Police as the Subject in Prevention of Child Abuse - Igrački, Jasmina (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
The paper examines the notion and forms of child abuse as one of the serious problems of contemporary societies. Particular emphasis is on the analysis of the causes and consequences of child abuse, as well as on the mechanisms of social reaction. During past decades, the reaction of society became more organised and systematic, both on the global and national level, aiming at the protection of children’s rights, who are the most vulnerable population. The paper analyses current legislation in the field of child protection in Serbia, which presents a relatively favourable framework for the protection of children from abuse, but which needs further work on the mechanisms for the implementation of new solutions in practice. Particular attention is paid to the system of criminal-legal protection of children with the focus on the role of the police in intervention, suppression and prevention of abuse and violence against children, as well as on the education of the police officers for adequate treatment of victims of violence and possibilities of their broader inclusion in recognizing potential abusers and recording them, as well as referring to social and judicial institutions in order to provide protection and prevention of child abuse.